ANALISIS VARIASI TEMPERATUR PRA MORDAN PEWARNA KAYU SECANG DAN DAUN JATI SERTA PENERAPAN HEDONIC TEST PADA KUALITAS SERAT KENAF INDUSTRI FASHION - Ida Rosanti; Ali Sadikin; Retno Prasetia (JURNAL AGRIMENT, 2020)
This study aims to determine the effect of pre-mordant material on kenaf fiber coloring using secang wood and teak leaves, to determine the Henodic Test method in classifying its quality, as well as to determine the significant effect on the color of kenaf fiber, and to determine the level of consumer preference for kenaf fiber. natural dyes. The research method used was an experiment with a variety of pre-mordant materials (alum, lime, vinegar). From the test, it was found that the color direction of the kenaf fiber was reddish purple to light brown, so the average value of fastness to washing was 4 (good). From this activity, it was concluded that the addition of secang wood and teak leaves as pre- mordant materials coupled with the effect of pH on the staining of kenaf fibers with secang wood extract provided variations in the direction of color and the value of color fastness to washing. Kenaf fiber is an environmentally friendly alternative to textile raw materials. This study used the Hedonic Test method with the Kruskal Wallis test. The results of this study were that there was no significant effect on the combination of compost application and pesticide application with natural dyes of secang wood and teak leaves on the color of kenaf fibers and there was no effect on the level of consumer preference for kenaf fiber with natural dyes.